Resolutions of complications in maxillary sinus lifting surgery: Clinical case report (Research, Society and Development, 2024)
The aim of this research is to show the resolution of complications during the surgical process in maxillary sinus lifting, where the main complication is the rupture of Schneider's membrane and the treatment is to cover this membrane with an LPRF collagen membrane (Platelet-rich fibrin and leukocytes). The methodology used to carry out the research is the Case Study. The present study shows how the surgical complication of sinus lift was treated. Currently in the dental field, the use of platelet concentrates is appreciated to assist in tissue and bone regeneration. Described by Choukroun, its properties are hemostasis, adhesion for the purpose of protection, and healing. This clinical case was attended at Instituto Peres, postgraduate courses, Goiânia.